New Perspectives on Risk Factors for Non-fatal Strangulation and Post-assault Imaging - McKee, Grace B. (Journal of interpersonal violence, 2022)
Strangulation has long been associated with death in the context of sexual assault and intimate partner violence (IPV). Non-fatal strangulation (NFS) during sexual assault, which refers to strangulation or choking that does not result in death, is common and has been associated with IPV and with bodily injury; however, other factors associated with NFS are unknown. The current study examined demographic and sexual assault characteristics associated with NFS among women who received a sexual assault medical forensic exam (SAMFE). A second purpose of this study was to explore factors associated with receiving follow-up imaging orders after NFS was identified during a SAMFE. Participants (N = 882) ranged in age from 18 to 81 (M = 28.85), with the majority identifying as non-Hispanic White (70.4%) or Black/African American (23.4%). A total of 75 women (8.5%) experienced NFS during the sexual assault. Of these, only 13 (17.3%) received follow-up imaging orders for relevant scans. Results from a logistic regression analysis demonstrated that NFS was positively associated with report of anal penetration, intimate partner perpetration, non-genital injury, and weapon use during the assault. Results from chi-square analysis showed that among sexual assaults involving women who experienced NFS, those whose assaults involved weapon use were over four times more likely to receive imaging orders compared to assaults without weapon use. These findings have implications for criminal justice, and if incorporated into danger assessments, could potentially reduce fatalities linked to sexual assault and/or IPV. Additional work is needed to ensure that all assaults with NFS trigger a referral for imaging regardless of other assault characteristics.